Ridged Zn/PDMS smart surface with wide-range reversible wettability and high sensitivity responsive to mechanical strain. (August 2020) - Lu, Chenxi; Li, Huihua; Yu, Senjiang; Jiao, Zhiwei; Li, Lingwei
Abstract: Smart surfaces with dynamically tunable wettability place an important role in microfluidics, biomedical engineering and flexible electronics. Mechanical strain is a promising stimulus to tune the surface wettability, however, it is still a great challenge to achieve both wide-range reversible wettability and high sensitivity. In this study, highly ordered and quasi-periodic ridge patterns with cracks at their peaks were tailored based on a film-substrate system by sputter deposition of zinc (Zn) nanofilm on prestretched polydimethylsiloxane (PDMS). The contact angle (CA) on the ridged Zn/PDMS surface is well tunable between 115° and 143° by adjusting the applied strains. It is remarkable that such a structure possesses wide-range CA variation (~28°) under just 28.6% applied strain, indicating a high responsive sensitivity ( η  = 98°). This result is attributed to the cracked ridges with both wide-range aspect ratios from 0.07 to 0.54 and high rate of change (~1.70). Moreover, the responsive reversibility of the ridged Zn/PDMS surface remains up to 1000 cycles and 60 days without special protection. The outstanding performances make the ridged surface could be a promising component for various technological applications, especially in small strain required situations. Graphical abstract: Unlabelled Image Highlights: Low cost and biocompatible materials (zinc and polydimethylsiloxane) are chosen to design the smart surface. A novel structure is tailored on the smart surface, namely cracked ridges. The ridged smart surface possesses wide-range reversible wettability and high sensitivity responsive to mechanical strain. The wetting mechanism on the ridged smart surface is investigated.